The Influence of Parentsâ€™ Educational Background and Giving Motivation to the Second Years Studentsâ€™ English Achievement at Junior High School 1 Sungai Aur - Dafrizal, Dafrizal; Roza, Wellya; Juhana, Juhana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to determine whether there is a positive and significant relationship between: 1) Parents' educational background on students' learning achievement in English, 2) Giving motivation to students' learning achievement in English, 3) Parents' educational background, giving Motivation towards student achievement in English. This case study research was conducted at Junior High School 1 Sungai Aur. The total population is all students of class VIII Junior High school 1 Sungai Aur as many as 204 people, the number of samples is 32 people. To find out whether there is a positive and significant relationship with the educational background of parents, presenting learning motivation with student achievement is used product-moment correlation analysis technique. From the results of the normality test, it is known that the data variables in the educational background of parents are normally distributed. To test the second hypothesis used product-moment correlation analysis. And to test the third hypothesis used multiple regression analysis techniques. The results showed that: 1) There was a positive and significant relationship between parents' educational background and student achievement.â€ The results of the correlation coefficient (rx1y) show that rcount is greater than rtable (0.396 > 0.349), 2) There is no positive and significant relationship between learning motivation and student achievement. The results of the correlation coefficient (rx1y) show that rcount is smaller than rtable (0.157 < 0.349), so there is no significant relationship, 3) There is no positive and significant relationship between parents' educational background, presenting learning motivation together with achievement student learning in English. The results based on the test obtained the F value of 3.771 and the significance of Fcount of 0.035. When compared with the Ftable value of 3.33, the Fcount > Ftable (3,771 > 3.33) and the significance value of Fcount less than 0.05 (0.035 < 0.05).